Digital principal instructional leadership in new normal era - Ahmad Nurabadi; Fendy Suhariadi; Antun Mardiyanta; Teguh Triwiyanto; Maulana Amirul Adha (Institute of Advanced Engineering and Science, 2022)
The needs for new knowledge and skill are driven by several factors and two most general are indefinite nature of SARS-CoV-2 and the need for alternative ways for students’ instruction during pandemic era. The two factors require principal to take their role differently. This study aimed to describe model of digital principal instructional leadership in new normal era. This was a quantitative study by using structural relation model, involved 290 teachers as sample of this study. Data were analyzed by using structural equation model (SEM) of AMOS 24.0. The study findings provided solid evidence that model of digital principal instructional leadership in new normal era is supported by field data. They also showed that respondents identify three crucial factors influencing the success of digital principal instructional leadership in new era. They are supporting online learning, proactive reducing issues of learning from home, and leading and managing virtual schools. Instructional leader should have adaptive capacity and flexibility to learn and develop during crisis. They should be able to give more effective response to overcome future challenges faced by the school institution.